1974
DOI: 10.1017/s0022029900014904
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties of casein micelles reformed from urea-treated milk

Abstract: SummaryMicelles reconstituted from urea-treated milk by exhaustive dialysis against bulk milk were similar to native micelles with respect to colloidal phosphate: casein ratio, ethanol stability, heat stability and susceptibility to first-stage rennin action. Reconstituted micelles were considerably smaller than native micelles as indicated by turbidity, sedimentation and viscosity, had shorter second-stage rennet coagulation times, were unstable to [Ca2+] > 20 mM and had reduced base-binding capacity. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Furthermore, treatment of milk at high hydrostatic pressure can result in considerable disruption of casein micelles (Huppertz et al, 2004a(Huppertz et al, ,b, 2006Anema et al, 2005), presumably also through solubilization of MCP (Huppertz et al, 2006). Disruption of casein micelles can also be achieved through disruption of hydrophobic interactions; for example, through addition of urea (McGann and Fox, 1974;Aoki et al, 1986;Holt, 1998;De Kruif and Holt, 2003) or SDS (Lefebvre-Cases et al, 1998, or heating milk to >60°C in the presence of >30% ethanol (O'Connell et al, 2001a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, treatment of milk at high hydrostatic pressure can result in considerable disruption of casein micelles (Huppertz et al, 2004a(Huppertz et al, ,b, 2006Anema et al, 2005), presumably also through solubilization of MCP (Huppertz et al, 2006). Disruption of casein micelles can also be achieved through disruption of hydrophobic interactions; for example, through addition of urea (McGann and Fox, 1974;Aoki et al, 1986;Holt, 1998;De Kruif and Holt, 2003) or SDS (Lefebvre-Cases et al, 1998, or heating milk to >60°C in the presence of >30% ethanol (O'Connell et al, 2001a,b).…”
Section: Introductionmentioning
confidence: 99%
“…In order to measure the stability of CCM against micelle disrupting agents, the sizes of CCM were analyzed by DLS after the addition of urea and citrate, and in alkaline conditions. As reported earlier, non-crosslinked CAS micelles dissociate after the addition of urea due to the disruption of hydrogen bonding and hydrophobic interactions, 44 as well as when the colloidal calcium is solubilized by chelating agents (e.g., citrate or EDTA) 45 or under strong alkaline conditions (pH∼12). 15 Figure 7a shows the intensity-based size distribution of CCM 14 before and after addition of urea, compared with non-crosslinked micelles.…”
Section: Stability Of the Ccmmentioning
confidence: 72%
“…Although the lack of equipment and a very poorly stocked library were major problems, there was a very good pioneering spirit at Moorepark, and I managed to get some research projects started, including a search for rennet substitutes, factors that affect the proteolysis of caseins by rennet, and the dissociation of casein micelles by urea and their reformation on removal of the urea by dialysis (Fox 1969a(Fox ,b, 1970Fox & Walley 1971a,b;McGann & Fox 1974). This work showed that bovine pepsin is a very good rennet substitute and was used widely, alone or mixed with chymosin, until the introduction of fermentation chymosin in approximately 1990 [which I also assessed (O'Sullivan ].…”
Section: Establishing a Research Career In Irelandmentioning
confidence: 99%
“…I have published approximately 60 research papers (e.g., see Fox & Morrissey 1972;Fox & Guiney 1972;O'Connor & Fox 1973;McGann & Fox 1974;Mulvihill & Fox 1979a;Murphy & Fox 1991;Lucey et al 1996;O'Connell et al , 2006Malin et al 2001;Zobrist et al 2005;Huppertz et al 2006b) and 25 reviews (e.g., see , Huppertz et al 2006a, Fox & Brodkorb 2008, Uniacke-Lowe et al 2010) on milk proteins. Volume 1 of Advanced Dairy Chemistry is devoted to milk proteins.…”
Section: Milk Proteinsmentioning
confidence: 99%